Pengaruh Semangat Kerja terhadap Kinerja Aparat di Kantor Desa Mattirowalie Kecamatan Maniangpajo Kabupaten Wajo - Fitra Ramadhani Atnes; H Yusran; Supris Musiapir; Muhammad Akram (Journal of Research and Development on Public Policy, 2026)
This study focuses on evaluating the level of influence of work spirit on the performance of officials at the Mattirowalie Village office, Maniangpajo District, Wajo Regency. This study uses a census research method, where the data source covers the entire population, all of which are covered as samples. The main approach of the statistical set used is the questionnaire. The pattern for this study included 10 people. The data collection methodology includes statements and questionnaires. This study uses quantitative descriptive and associative methods as its statistical assessment strategy. The usefulness of this research includes all practical and theoretical components. The real benefits of this research are: a. For the author, it is an encouragement to further improve understanding in writing scientific papers in the form of research thesis, b. For other parties, namely if they can contribute as a reference for further research, the academic implications of this research include to improve standards or theories that help improve labor control, technology, especially regarding the influence of work spirit on the performance of the apparatus at the Mattirowalie village office, Maniangpajo District, Wajo Regency. The research findings explain the positive impact of Work Spirit on the Performance of Apparatus at the Mattirowalie Village Office, Maniangpajo District, Wajo Regency.